Large-scale transcriptome-wide association study identifies new prostate cancer risk regions - Nicholas Mancuso (Nature Portfolio, 2018)
Genome-wide association studies (GWAS) have identified hundreds of genomic risk regions for prostate cancer. Here, the authors perform a transcriptome wide association study (TWAS) by incorporating prostate cancer GWAS with gene expression data to identify potential novel prostate cancer risk loci and possible risk mechanisms.